IBM KELOMPOK USAHA PEMBUATAN WINGKO BABAT DI KOTA SEMARANG - Arief, Ulfah Mediaty; Purbawanto, Sugeng; Setyaningsih, Dyah Nurani (Universitas Negeri Semarang, 2015)
Implementation of the program is aimed at solving problems IbM exist in the industry wingko babat for small industries that took place in the industry wingko babat stamp pack “Lokomotif” owned Slamet Riyono located on Jl . Brotojoyo IV / 3 Semarang ( UKM 1 ) and wingko babat Babat “ Pak Moel “ Jl . Central Pekunden 1106 Semarang ( UKM 2 ) as a partner for existing Wingko Babat at semarang group . This method IbM program is disseminating the program , design mixer ( mixer ) wingko Babat with a capacity of ± 100 kg as an effort to improve the quality and quantity of industrial production wingko Babat in Semarang “ , then tested as a training and demonstration plotting mixer ( mixer ) which is performed in industry wingko babat stamp “Lokomotif” . The results of this trial showed that mixing homogeneity quite fit the industry standard and quality that matches the flavor industry . Training aspects of business management , namely financial management accounting practice , the parties will have a balance of UKM partners every week , or month , or year